REFLEKSI PERAN PEREMPUAN DALAM NOVEL INDONESIA 1900–2000 - Else Liliani (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2010)
This study aims to describe women’s roles, problems, and ways to solve the problems reflected in Indonesian novels in the period of 1900–2000. The data sources were 20 top novels published in that period. The data were collected through reading and analyzed by relating them to several elements as their contexts and using the analytical construct in the feminist literary criticism. The results are as follows. First,women’s public roles include their participation in the movements, education, and business and their domestic roles are as wife and mother. Second, their domestic problems are related to psychological problems, nationality, gender construction, domestic violence, and financial dependence. Third, the problems result from differences in nationality, society’s patriarchal culture, religious interpretation, gender construction, politics, and financial dependence. Fourth, the characters’ attitudes to the problems are in the form of submission, opposition, and escapism.